2013
DOI: 10.1093/infdis/jit373
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Viremia and the Risk of Chronic Kidney Disease in HIV-Infected Individuals

Abstract: Compared with HIV-infected subjects who were HCV seronegative, both HCV viremic and HCV aviremic individuals were at increased risk for moderate and advanced CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 36 publications
1
41
2
1
Order By: Relevance
“…We did not have HCV RNA data to confirm chronic HCV infection, and it is likely that hepatitis C resolved in some patients. However, the NA-ACCORD study recently reported that individuals who were HCV Ab positive but HCV RNA negative also had an increased risk for CKD similar to individuals who were HCVAb and RNA positive [30]. In addition, our results may not generalize to nonveterans, women, children or patients not receiving regular clinical care.…”
Section: Discussionmentioning
confidence: 70%
“…We did not have HCV RNA data to confirm chronic HCV infection, and it is likely that hepatitis C resolved in some patients. However, the NA-ACCORD study recently reported that individuals who were HCV Ab positive but HCV RNA negative also had an increased risk for CKD similar to individuals who were HCVAb and RNA positive [30]. In addition, our results may not generalize to nonveterans, women, children or patients not receiving regular clinical care.…”
Section: Discussionmentioning
confidence: 70%
“…The majority of previous studies of HCV and kidney disease outcomes have defined HCV based on antibody status, and studies evaluating the independent effect of HCV viremia have yielded conflicting results. (15,16) Nonetheless, the sensitivity of ICD-9-CM codes for the diagnosis of HCV infection has not been well established. Although a study in the US Veterans Affairs Health System demonstrated reasonable positive and negative predictive value to identify patients with a known diagnosis of HCV infection, that study included both inpatient and outpatient data from the longitudinal patient record.…”
Section: Discussionmentioning
confidence: 99%
“…In ESRD patients on maintenance dialysis, the prevalence of HCV increases with dialysis duration [16] , potentially due to transmission from blood products or contaminated equipment [11] . Additionally, certain populations are at increased risk of both diseases, including those with human immunodeficiency virus (HIV) and those who engage in intravenous drug use [17] . The presence of both HCV and CKD can make treatment difficult [11,18,19] due to tolerance and exacerbations associated with certain treatments [20,21] .…”
mentioning
confidence: 99%